Sistem Pengelolaan Dana Zakat Pada Badan Amil Zakat Nasional Kota Palu - Sandang, Mufrih; Sabir, Sabir; Tahimu, Muhammad Reza; Ubay, Ubay; Arman, Muhammad (Journal of Islamic Community and Development, 2025)
This research discusses “The Zakat Fund Management System at the National Amil Zakat Agency (BAZNAS) of Palu City.” The main problems are divided into several subtopics: (1) how the zakat collection system is implemented by BAZNAS Palu City, (2) how zakat distribution is carried out in Palu City, and (3) what obstacles and efforts are made by BAZNAS Palu City in managing zakat. This study employs a qualitative descriptive approach with data collected through observation, interviews, and documentation. The data sources consist of primary and secondary data, while data analysis is conducted through stages of data reduction, presentation, and conclusion drawing to produce systematic findings. The results show that zakat fund management by BAZNAS Palu City has been carried out effectively by the Zakat Collection Unit (UPZ) and its distribution through various programs such as Palu Sejahtera, Palu Cerdas, Palu Bertakwa, Palu Sehat, and other initiatives. In its implementation, BAZNAS Palu City faces several challenges but continues to make efforts to overcome them. It is recommended that BAZNAS Palu City enhance its efforts to raise public awareness about the importance and benefits of paying zakat through various media, such as social media, the official BAZNAS website, and direct outreach activities, as well as expand the scope of its programs to increase the number of beneficiaries in Palu City.